The impact of E-Recruitment process of Brac on Generation- Z and millennials to pursue jobs in Bangladesh - Yeasmin, Farzana (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.